2022
DOI: 10.3749/canmin.2000097
|View full text |Cite
|
Sign up to set email alerts
|

Raman Geobarometry of Quartz Inclusions in Kyanite: Application to Quartz Eclogite from the Gongen Area of the Sanbagawa Belt, Southwest Japan

Abstract: Residual pressure values of quartz inclusions in host kyanite were estimated using Raman spectroscopy and show that the quartz-inclusions-in-kyanite system can be used as a geobarometer for estimating peak metamorphic conditions. Samples of quartz eclogite, a pelitic high-pressure metamorphic rock composed mainly of garnet, omphacite, and quartz, with subordinate kyanite, were obtained for analysis from the Gongen area in the Sanbagawa metamorphic belt, southwest Japan. Residual pressure in the 236 analyzed qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In this report, we describe needle rutile inclusions in garnet within a quartz-eclogite from the Sanbagawa metamorphic belt in central Shikoku. Many previous petrological studies showed that the eclogite in the Sanbagawa metamorphic belt in central Shikoku has not been reached UHP conditions (e.g., Miyamoto et al, 2007;Tomioka et al, 2022). The characteristics of rutile exsolution lamellae along with the chemical composition of garnet that have not experienced UHP/UHT conditions reported in this study will improve our understanding of Tiin-garnet behavior during high-grade metamorphism.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this report, we describe needle rutile inclusions in garnet within a quartz-eclogite from the Sanbagawa metamorphic belt in central Shikoku. Many previous petrological studies showed that the eclogite in the Sanbagawa metamorphic belt in central Shikoku has not been reached UHP conditions (e.g., Miyamoto et al, 2007;Tomioka et al, 2022). The characteristics of rutile exsolution lamellae along with the chemical composition of garnet that have not experienced UHP/UHT conditions reported in this study will improve our understanding of Tiin-garnet behavior during high-grade metamorphism.…”
Section: Introductionmentioning
confidence: 56%
“…The Sanbagawa belt in Shikoku has been studied for more than half a century without discovering any coesite, and quartz-eclogite in this area has been reported to be below ultrahigh pressure (Miyamoto et al, 2007;Tomioka et al, 2022). Thus, the identification of rutile exsolution lamellae in garnet grown under eclogite facies conditions from the Sanbagawa belt provides important material evidence that the conditions for the occurrence of rutile exsolution lamellae in nature are satisfied under non-UHP/UHT conditions.…”
Section: A C C E P T E D I N J M P S P R E -P R O O Fmentioning
confidence: 99%